Value of 3-mg, Stilbestrol implants for young lambs - Menzies, C.; Hillman, M.; Lenhart, D. (Kansas Agricultural Experiment Station, 2011)
Forty-two crossbred lambs sired by Suffolk rams and out of commercial fine-wool ewes were used. Twenty-one were implanted with 3 mgs. Stilbestrol each. Lambs averaged 24 days of age when started on test, February 17. They nursed their mothers until May1, when all were weaned. A pelleted ration of 45% sorghum grain, 2.5% soybean oil meal, 7.5% molasses, 45% dehydrated alfalfa meal, and 10 mgs. aureomycin per pound was self-fed in a creep before lambs were weaned and in a self-feeder after that. Loose alfalfa hay was fed free choice in addition to the pellets.
Keywords: Sheep; Stilbestrol implants; Hormone treatments